Use of Medications for the Treatment of Alcohol Dependence: A Retrospective Study Conducted in 2011-2012 - Agabio, Roberta; Balia, Silvia; Gessa, Gian L.; Pani, Pier Paolo (Current Drug Research Reviews, 2021)
Background: Pharmacotherapy for Alcohol Dependence (AD) is underutilized. Barriers preventing the use of AD medications include high prices, lack of access to prescribing physicians, and a limited number of available medications. Objective: The study evaluated the use of AD medications in a sample of Italian outpatients who received these medications free of charge, had access to physicians during office hours, and for whom substitution therapy [gamma-hydroxybutyrate (GHB)] was available. We also evaluated the rate of patients who received a combination of non-pharmacological and pharmacological treatments among participants who were still drinking. Methods: SCID for AD and questionnaire were filled by to AD outpatients during a face-to-face interview. Results & Discussion: 345 AD outpatients were interviewed: 58.8% were currently receiving at least one AD medication (GHB: 34.3%, disulfiram: 29.6%, acamprosate: 5.9%; naltrexone: 2.5%; more than one medication: 16.7%). Less than 30% of participants who were still drinking, received a combination of non-pharmacological and pharmacological treatments. Nonetheless, we found higher use of AD medications compared to previous studies conducted in other countries. This higher use of AD medications may be due to access to free medications, prescribing physicians’ style, and a larger number of available medications. Conclusion: Our results confirm the underutilization of AD medications, as less than 60% of AD outpatients received medications, and less than 30% of those who were still drinking, received a combination of non-pharmacological and pharmacological treatments. These findings may be useful in improving our knowledge of the barriers that prevent the use of AD medications in clinical practice.
Keywords: pharmacotherapy